Study guides

Q: What is the answer to x cubed plus 3x squared plus 3x plus 2 divided by x plus 2?

Write your answer...

Submit

Related questions

3x3+15x2+18x = 3x(x2+5x+6) = 3x(x+2)(x+3)

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

9x(x2+3x-10)

x3+3x2+6x+1 divided by x+1 Quotient: x2+2x+4 Remaider: -3

4x(4x^2 + 3x + 1)

(x + 2)(3x - 1)(3x + 1)

The 3x is cubed and the 4x is squared

24

the answer is (3x-2)(9x squared+6x+4)

(8x + 9)(3x^2 - 1)

Locate the turning point(s) for the following functions. (a) y=x3-x2 -3x + 5 3

x³ + x² - 3x - 3 = (x + 1)(x + √3) (x - √3).

Factorise it: (x + 5)(3x - 8)

5x2 + 3x + 8x2 = 13x2 + 3x = x(13x + 3)

The given expression can be simplified to: 3X squared +27

(12x2 + 18) / (3x2 + 6) = (4x2 + 6) / (x2 + 2)

9x2 + 3x / 3x equals (3x + 1).9x2 + 3x divided by x is 9x + 3 , and then divided by 3 yields the 3x +1.

3

(3x - y+ 2)(3x + y + 2)

3x2.

12

5x3 - 3x2 + 2x = x*(5x2 - 3x + 2) The quadratic has no real factors.

(3x + 3y)(x + y) = 3(x + y)2

The given expression can be simplified to: 8x squared +9

(3x + 1)(x + 5)